The Political Dimension of an Enterprise’s Collective Agency - de Lastic, Adélaïde (Phenomenology and Mind, 2019)
What is the political dimension of an enterprise if it is taken as a collective agent? Referring to political collective agency, we can’t ignore the case of enterprises. Indeed, they have a collective agency, as we firstly point out in this article. The collective agency of the enterprise impacts the world in different ways that we secondly consider in this article. Enterprises have an impact on states, on citizens, on health, on the environment. They have an impact on employment and on the economy. As such, they contribute to the life of society. In the same way, law impacts them, but also consumers’ choices and local socio-economic context. In fact, enterprises must be concerned by corporate social responsibility, they have to care about human’s commons and this is a political issue without borders: it is today a prominent political question of equity for the citizen of the world. I offer an ontological account of political collective agency applied to the enterprise. According to this account, an enterprise is a specific kind of social object, which has several intrinsic properties. Put together these properties enable the enterprise to act as a group with a definite political significance.